Reframing housing struggles: Right to the city and urban citizenship in Santiago, Chile. Issue 5 (3rd September 2017) - Pérez, Miguel
Abstract : After Augusto Pinochet's dictatorship (1973–1990), Chile's post-dictatorial governments drew on market-based policies to develop large-scale subsidised housing projects and, accordingly, avoid the reappearance of mass housing movements. However, the considerable building of subsidised social housing in the 1990s did not lead to better living conditions for pobladores (the urban poor). To become homeowners, they began to be systematically expelled from their neighbourhoods of origin and relocated to segregated peripheries. This phenomenon has resulted in the re-emergence of housing protests in the last decade, which are mostly organised around pobladores ' demands for staying in their neighbourhoods. This paper analyses such a remobilisation process by scrutinising ethnographically the case of a state-regulated housing assembly in La Florida, a district of Santiago undergoing a housing affordability problem due to the generalised increase in land prices in Santiago's Metropolitan Area. It focuses on how pobladores ' demands for the right to stay put in La Florida account for a broader reframing of right-to-housing struggles, expressed in the growing incorporation of right-to-the-city claims in their political language. In doing so, I show that current urban struggles allow for the rise of a type of urban citizenship through which the urban poor, by conceiving of themselves as city-makers, generate particular understandings of themselves as rights-bearers. This process of citizen formation, however, is paradoxical: although it is the result of mobilisations aimed at contesting market-based policies, it is permeated by a neo-liberal ethics through which the urban poor legitimate themselves as urban citizens.